Effect of chlorhexidine chip as an adjunct in non-surgical management of periodontal pockets: a meta-analysis - Lili Ma; Xiuchun Diao (BMC, 2020)
Abstract Background The aim of this meta-analysis was to evaluate the difference in treatment outcomes between sub-gingival placement of chlorhexidine chip (CHX chip) in adjunct to scaling and root planing (SRP) and SRP alone for the management of periodontal pockets in patients suffering from chronic periodontitis. Methods We searched the MEDLINE (PubMed), SCOPUS and CENTRAL databases and identified 15 randomized clinical trials published within the last decade (2007-2019): 9 with split-mouth design and 6 with parallel study design. We extracted data and performed both qualitative and quantitative syntheses. The primary outcomes assessed were gain in clinical attachment level (CAL), reduction in probing pocket depth (PPD), improvement in gingival inflammation, and results of microbiological assays. Results We used meta-analysis plots to assess all the clinical outcomes. The mean differences in PPD reductions at 1 month (MD 0.63), 3 months (MD 0.69), and 6 months (MD 0.75); and the CAL gains at 1 month (MD 0.54), 3 months (MD 0.64), and 6 months (MD 0.68) showed more favorable responses in sites treated with the CHX chip as an adjuvant to SRP, than in sites treated with SRP alone. Conclusion SRP with adjunctive CHX chips showed better clinical outcomes than SRP alone for the management of periodontal pockets in patients with chronic periodontitis.